Identification of the Spectrotemporal Modulations That Support Speech Intelligibility in Hearing-Impaired and Normal-Hearing Listeners - Venezia, Jonathan H. (J Speech Lang Hear Res, 2019)
PURPOSE: Age-related sensorineural hearing loss can dramatically affect speech recognition performance due to reduced audibility and suprathreshold distortion of spectrotemporal information. Normal aging produces changes within the central auditory system that impose further distortions. The goal of this study was to characterize the effects of aging and hearing loss on perceptual representations of speech. METHOD: We asked whether speech intelligibility is supported by different patterns of spectrotemporal modulations (STMs) in older listeners compared to young normal-hearing listeners. We recruited 3 groups of participants: 20 older hearing-impaired (OHI) listeners, 19 age-matched normal-hearing listeners, and 10 young normal-hearing (YNH) listeners. Listeners performed a speech recognition task in which randomly selected regions of the speech STM spectrum were revealed from trial to trial. The overall amount of STM information was varied using an up–down staircase to hold performance at 50% correct. Ordinal regression was used to estimate weights showing which regions of the STM spectrum were associated with good performance (a “classification image” or CImg). RESULTS: The results indicated that (a) large-scale CImg patterns did not differ between the 3 groups; (b) weights in a small region of the CImg decreased systematically as hearing loss increased; (c) CImgs were also nonsystematically distorted in OHI listeners, and the magnitude of this distortion predicted speech recognition performance even after accounting for audibility; and (d) YNH listeners performed better overall than the older groups. CONCLUSION: We conclude that OHI/older normal-hearing listeners rely on the same speech STMs as YNH listeners but encode this information less efficiently. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.7859981